Litterfall and litter in forest restoration sites in Mato Grosso do Sul, Brazil - Costa, Poliana Ferreira da; Pereira, Zefa Valdivina; Fernandes, Shaline Séfara Lopes; Fróes, Caroline Quinhones; Barbosa, Thiago Oliveira; Santos, Bruna Souza dos (Revista Ecologia e Nutrição Florestal - ENFLO, 2020)
This study aimed to evaluate the potential of litter and litterfall as ecological indicators in three sites in restoration process located in Ivinhema, Jateí and Caarapó – Mato Grosso do Sul state, Brazil, after 12, 13 and 16 years of implantation, respectively. The objective was also to obtain Pearson's simple linear correlation) between monthly litterfall with environmental variables of rainfall and air temperature. To litterfall sampling, 15 litter traps were used (0.80 m x 0.80 m) and, for litter sampling, six collections were carried out in each restoration site, in December 2016, using a frame (0.64 m2). The samples were separated into three components: leaves, twigs, reproductive material (flowers and fruits). The high litter amount, in the three sites evaluated (Ivinhema 9.4 Mg ha-1; Jatéi 5.5 Mg ha-1; and Caarapó 7.1 Mg ha-1), demonstrates the importance of litterfall and litter as an indicator for the stages initial succession in restored forests. There were weak correlations between litter and environmental variables, being negative for air temperature and positive for rainfall. This study aimed to evaluate the potential of litter and litterfall as ecological indicators in three sites in restoration process located in Ivinhema, Jateí and Caarapó – Mato Grosso do Sul state, Brazil, after 12, 13 and 16 years of implantation, respectively. The objective was also to obtain Pearson's simple linear correlation) between monthly litterfall with environmental variables of rainfall and air temperature. To litterfall sampling, 15 litter traps were used (0.80 m x 0.80 m) and, for litter sampling, six collections were carried out in each restoration site, in December 2016, using a frame (0.64 m2). The samples were separated into three components: leaves, twigs, reproductive material (flowers and fruits). The high litter amount, in the three sites evaluated (Ivinhema 9.4 Mg ha-1; Jatéi 5.5 Mg ha-1; and Caarapó 7.1 Mg ha-1), demonstrates the importance of litterfall and litter as an indicator for the stages initial succession in restored forests. There were weak correlations between litter and environmental variables, being negative for air temperature and positive for rainfall.